Tokyo ever after - Jean, Emiko (Jean, Emiko. Tokyo ever after, 2021)
After learning that her father is the Crown Prince of Japan, Izumi travels to Tokyo, where she discovers that Japanese imperial life--complete with designer clothes, court intrigue, paparazzi scandals, and a forbidden romance with her handsome but stoic bodyguard--is a tough fit for the outspoken and irreverent eighteen-year-old from northern California.